RESEARCH OF THE SYNTHESIS OF NITROGEN, PHOSPHORUS, AND SULFUR CONTAINING OLIGOMERS (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
Oligomer is a low molecular weight substance with the same chemical structure as polyester fiber, which is a by-product of the polyester spinning process. This article talks about oligomers, their composition of nitrogen, sulfur, phosphorus, synthesis process and their structure.